Innovative Potential of Modern Cultural Strategies: Ukrainian Context - Kozyntseva, Tetiana; Synakh, Andrii; Dulebova, Irina (Socio-Cultural Management Journal, 2021)
Introduction. The creative and cultural industries have made significant adjustments to the modern world economic processes, which provokes an increased interest in the cultural sphere in general and in the cultural strategy in particular. Purpose and methods. The purpose of the article is to identify the innovative potential of culture in modern conditions and its implementation ways through cultural strategies and creative industries, both in the universal and in the Ukrainian context. The methodological basis of the study was the systemic-structural method, the method of formal-logical research, analysis, the comparative method, the system-thought-activity methodology, and the deconstructive approach. Results. An integrated approach to culture allows considering it as an open space for the interaction of people, ethnic groups, nations that are the subjects of economic, political, and cultural innovation. Cultural development is represented through vertical-horizontal interactions between cultural strategy, cultural policy, and creative industries. Conclusions. The Ukrainian State is currently rethinking the role of culture in general and cultural strategy in particular, facing the problem of forming an integral Ukrainian-oriented space. The new approach to the structure of culture includes not institutions, but the creators and consumers of the cultural product, who initiate a single cultural space creation. That allows identifying the innovative potential of culture and cultural strategy. Ukraine’s innovative cultural strategy and its implementation through cultural policy and creative industries can serve both to consolidate society and to solve economic problems.